Purification of boron nitride nanotubes by functionalization and removal of poly(4-vinylpyridine) - Lee, Soul-Hee; Kang, Minsung; Lim, Hongjin; Moon, Se Youn; Kim, Myung Jong; Jang, Se Gyu; Lee, Hyo Joong; Cho, Hyunjin; Ahn, Seokhoon (ELSEVIER, 2021)
BNNTs were functionalized by using a polymer that includes a pyridine group, which can undergo dipole interactions with boron atoms in BNNTs. The functionalized BNNTs were well-dispersed in an alcohol solvent, whereas hexagonal boron nitride impurities precipitated, due presumably to stacked structures. After purification processes, acid was added to a solution that contained functionalized BNNTs to prevent pyridine-boron interactions through stronger acid-base interactions. Thus, the polymer bound to the BNNTs was easily separated, and purified BNNTs could be obtained using a solution process.
Keywords: LARGE-SCALE SYNTHESIS; SURFACE MODIFICATION; HIGH-PERFORMANCE; H-BN; NANORIBBONS; PRESSURE; HYDROGEN; GROWTH